Effects of compost sources as a component of seedling growing media and fertilizer on growth performance of cauliflower (Brassica Oleracea L. var. Botrytis) - Abdul Mutalib, Farahzety (2014)
The use of agricultural wastes into renewal agricultural products such as fertilizer and growing medium can contribute towards reducing the import bill and safer food as well as avoiding environmental pollution. Two experiments were carried out to assess the effects of five different agriculture waste composts as a nursery media component and source of organic fertilizer for production of cauliflower under protective structure. The five different compost sources used were oil palm empty fruit bunches compost (EFBC), chrysanthemum residue compost (CRC), soybean waste compost (SWC), green waste vermicompost (GWV) and vegetable waste vermicompost (VWV). For cauliflower transplant production, the growth media comprised of a mixture with ratio of 30% compost to 70% sphagnum peat moss (v/v) and 100% of sphagnum peat moss was used as a control. The treatments were laid out in randomized complete block design (RCBD) and replicated four times. Results showed that substitution of peat with compost increased bulk density, available water, porosity and nutrients content of media mixtures. The CRC added media and 100% peat were found to have similar physical characteristics, electrical conductivity (EC) and nutrient content. The highest seedling height, total leaf number, total leaf area, and shoot dry weight were recorded in both CRC mixture and peat media. However, CRC mixture significantly (P<0.05) improved root morphology of cauliflower seedlings compared with those grown in other substrate mixtures. Results showed that peat could be 30% partially substituted by CRC, EFBC, GWV or VWV however the use of SWC can negatively affect plant growth. The physical and chemical properties of SWC added media were found to be unsuitable for seedling growth due to the higher pH, EC and bulk density. This study indicated that composts enhanced seedling growth in several occasions and these growth enhancements could be attributed to the improvement of the physical and chemical properties of the growing media. Similar compost sources were used as organic fertilizer to assess the effects on the soil properties, nutrient status, growth performance and yield of cauliflower under a protective structure. Composts (EFBC, CRC, SWC, GWV and VWV) as source of fertilizer were applied prior to transplanting and an inorganic fertilizer (N: P2O5: K2O: MgO; 12:12:17:2:TE) was used as a control. The treatments were laid out in randomized complete block design (RCBD) replicated three times. The amount of fertilizer applied was calculated based on 180 kg N ha-1. Results indicated that, the use of composts as organic fertilizer significantly affected soil properties, plant growth, photosynthetic capacity, nutrient status and yield of cauliflower. Application of VWV significantly (P<0.05) affected shoot development of cauliflower planted under protective structure. The growth performance of cauliflower receiving vegetable waste vermicompost (VWV) was similar with those receiving inorganic fertilizer in plant height and plant biomass and greater in total leaf area. The nutritional status of the plants demonstrated that the nutrients were adequate and met the requirements for plant growth and curd development in all fertilizer treatments. Highest curd weight was found with VWV application however, it did not differ significantly with EFBC and inorganically fertilized plants. Both EFBC and VWV applications enhanced the ascorbic acid content. However, curds of VWV could be harvested earlier compared to the other treatments. From the results, composts could produce similar crop growth and yields as inorganic fertilizer when the same amount of N was applied to the plants. However, the effects of compost on plant growth and yield were not always positive and might vary depending on the source of waste, compost maturity and available N of the compost.